A case of severe acute hemorrhagic duodenitis after administration of immune checkpoint inhibitor. Issue 1 (22nd August 2021) - Saito, Keita; Nagumo, Hironobu; Iwasaki, Miyuki; Nishiwaki, Takuro; Ozono, Daiki; Inoue, Shin; Yoshimura, Souhei; Kishita, Hideyuki; Nakachi, Kenichiro; Harasawa, Hisato; Kawamitsu, Natsuki; Yoshimura, Shigenobu; et al.
ABSTRACT: Case : A 66‐year‐old man started carboplatin + etoposide + atezolizumab therapy for advanced small cell lung cancer. Seventeen days after the start of treatment, the patient presented with hematemesis and underwent emergency endoscopy, which revealed multiple erosions and ulcers in the duodenum. Some ulcers showed pulsating bleeding, which was stopped by clipping and cauterization using hemostats. Biopsy of the mucosal peri‐ulcer showed lymphocyte, eosinophil, and plasma cell infiltration. The patient was suggested to have acute hemorrhagic duodenitis, which was associated with immune checkpoint inhibitors (ICIs), and conservative treatment with blood transfusion and antacids was continued. However, 11 days after hemostasis, bleeding from a new ulcer was observed. Hemostasis was achieved by coagulation and clipping again, but the general condition of the patient deteriorated owing to the rapid progression of the primary disease, and he died 8 weeks after the start of treatment. Discussion : Although there have been several reports of colitis and other adverse events caused by ICIs, there have been very few reports of duodenitis. Endoscopic findings include diffuse erythema, erosions/ulcerations, and villous atrophy, and pathological findings include eosinophilic infiltration and increased levels of CD8‐positive T cells. However, there have been no reports of duodenal mucosal damage caused after administration of atezolizumab nor of severe cases of massive bleeding requiring endoscopic hemostasis and blood transfusion, as in this case.